The Dream of God: How Do Religion and Science See Lucid Dreaming and Other Conscious States During Sleep? - Mota-Rolim, Sergio A.; Bulkeley, Kelly; Campanelli, Stephany; Lobão-Soares, Bruno; de Araujo, Draulio B.; Ribeiro, Sidarta (Frontiers in Psychology, 2020)
Lucid dreaming (LD) only began to be scientifically studied in the last century, but various religions have highlighted the importance of LD in their doctrines for a much longer period. Hindus’ manuscripts dating back over two thousand years ago, for example, divide consciousness in waking, dreaming (including LD), and deep sleep. In the Buddhist tradition, Tibetan monks have been practicing the “Dream Yoga”, a meditation technique that instructs dreamers to recognize the dream, overcome all fears when lucid, and control the oneiric content. In the Islamic sacred scriptures, LD is regarded as a mental state of great value, and a special way for the initiated to reach mystical experiences. More recently, some branches of the Spiritism religion argue that LD precedes out-of-body experiences during sleep. Here we reviewed how these and other religions interpret dreams and LD. We observed that while Abrahamic monotheisms (Judaism, Christianism, and Islamism) recognize dreams as a way to communicate with God to understand the present and predict the future, the traditional Indian religions (Buddhism and Hinduism) are more engaged in cultivating self-awareness, thus developed specific techniques to induce LD.